Kindergarten teachers' perception and practice of play-oriented instruction implications for teachers development - Avestros, Viola S. (College of Education, University of the Philippines Diliman, 2019)
A study 44 public school kindergarten teachers in the Science City of Munoz, Nueva Ecija, explored the perception and practice of play-oriented classroom instruction in kindergarten. Data gathered through survey and classroom observations revealed the following perceptions: 1) participants generally perceive play-oriented classroom activities as beneficial to kindergarten pupil's learning and development, 2) majority of the participants consider themselves adept in implementing play activities, 3) many of the participants consider use of worksheets, listening to teacher's discussion and oral recitation as play-oriented activities and 4) despite their perceived adeptness in implementing play-oriented activities, most of the participants believe in the need for play to be included in training with topics on play instruction, music and movement, and various play activities for kindergarten. Data gathered from the survey, interviews, and classroom observations revealed that the perception of the teachers of the teachers on play-oriented instruction is generally positive and teacher's practice of play in the classroom comes in varied but limited forms. Based on the findings on kindergarten teachers' nature of understanding of play-oriented instruction, a proposed training workshop was designed to enrich their knowledge and skills so they can deliver the kindergarten curriculum in more developmentally appropriate ways.